The effect of road hump in reducing speed of motorcars in a residential area in Kuala Lumpur - Yaacob, Noor Alyani; Kadar Hamsa, Abdul Azeez (Faculty of Built Environment, University of Malaya, 2013)
In its most simple terms, traffic calming is about preserving the functions of local streets. As local streets are intended to provide primarily land-access services, hence, when traffic begins to use local streets for through movements, traffic volume and speed levels become incompatible with this primary function. To respond, a study on the effectiveness of traffic calming measures in reducing vehicles speed at Taman Setapak residential area was undertaken. Field observations and spot speed survey were conducted to collect primary data. The field observation was carried out to collect data on road geometrics and design characteristics of the road humps. The spot speed survey was administered to collect vehicles speed at different points near the road humps. The major findings include first, the road humps proved effective in reducing the speed of the vehicles and second the design characteristics of the road humps is an important factor in reducing the speed of the vehicles. The average speed of the vehicles before approaching the road humps was about 30 km/hr and at the road humps below 10 km/hr. The findings showed that the design profiles of the road humps have an impact on the speed of the vehicles; the gentle the design profiles of the road humps especially in terms of its height and slope, the higher the speed of the vehicles near and at the road hump. The findings also showed a clear difference in the average speed of the motorcars approaching the road hump and at the road hump.